Teaching History in Moroccan Secondary Education in Light of Universal Design for Learning: An Analytical Diagnostic Study - The Humanities and Literature Track as a Model - Saffour, Mhamed; Bahou, Abdellaziz; El-Amrani, Abdelaziz Alaoui (Journal of Curriculum and Teaching Methodology, 2025)
This research aimed to diagnose and analyze the current state of history teaching in Moroccan high schools in light of the Universal Design for Learning (UDL) approach. To achieve this, the researcher employed a descriptive-analytical methodology, using a content analysis grid for the document "Educational Guidelines and Programs for Teaching History and Geography in Secondary Education" and another grid for the history textbook for the common trunk of humanities and social sciences. Additionally, a classroom observation grid was used to monitor the nature of classroom practices of history teachers in light of the UDL approach, supported by a questionnaire for the same sample. A self-assessment grid for students in the common trunk of humanities and social sciences was another employed tool. The research sample included 51 history teachers in the directorates of Ifrane and guercif, along with 88 students in the same geographical area. The sample also included the document "Educational Guidelines and Programs for Teaching History and Geography in Secondary Education" and the first part of the history textbook for the common trunk of humanities and social sciences. The researcher found that history teaching in Moroccan high schools does not fully incorporate the principles of the UDL approach, which explains students' perception of it as a monotonous and unattractive subject. In light of these findings, the researcher recommends a radical change in the history curriculum by integrating the principles of UDL, along with the importance of training both practicing and prospective teachers to apply this pedagogical approach.
Keywords: History teaching; High school level; Universal Design for Learning (UDL) approach; Common trunk of humanities and social sciences